2023
DOI: 10.1186/s40104-023-00867-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tannic acid on the immunity and intestinal health of broiler chickens with necrotic enteritis infection

Abstract: Background In broiler chickens, necrotic enteritis (NE) infection can reduce production performance. Tannic acid has shown great potential as a treatment of NE in broilers. However, the appropriate dosage of tannic acid in NE of broilers and the improvement effect on intestinal health are not very clear. In this study, we aimed to investigate the effects of different doses of tannic acid on the production performance, immunity, and intestinal health of broilers by constructing an NE model with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Our results showed that the addition of 3.0 kg/t TA to the diet significantly reduced certain pathogenic bacteria, such as Candidatus Brocadia, [Eubacterium] oxidoreducens group, and Escherichia-Shigella in cecal digesta. These results also support that TA can effectively inhibit the growth of harmful bacteria and maintain intestinal microbial homeostasis in weaned piglets [16], which could also explain why TA has better intestinal morphology and lower pro-inflammatory cytokines than CON. Notably, olive extracts enriched various polyphenolic compounds (especially Hydroxytyrosol) could improve antioxidant capacity and attenuate oxidative stress by altering colonic microbiota in mice [52,53], suggesting that gut microbiota play an important role in modulating redox homeostasis under dietary polyphenolic compounds treatment.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our results showed that the addition of 3.0 kg/t TA to the diet significantly reduced certain pathogenic bacteria, such as Candidatus Brocadia, [Eubacterium] oxidoreducens group, and Escherichia-Shigella in cecal digesta. These results also support that TA can effectively inhibit the growth of harmful bacteria and maintain intestinal microbial homeostasis in weaned piglets [16], which could also explain why TA has better intestinal morphology and lower pro-inflammatory cytokines than CON. Notably, olive extracts enriched various polyphenolic compounds (especially Hydroxytyrosol) could improve antioxidant capacity and attenuate oxidative stress by altering colonic microbiota in mice [52,53], suggesting that gut microbiota play an important role in modulating redox homeostasis under dietary polyphenolic compounds treatment.…”
Section: Discussionsupporting
confidence: 65%
“…However, studies increasingly found that appropriate doses of TA can reduce diarrhea incidence and improve gut health without any adverse effect on the growth performance of piglets [12][13][14][15]. The observed positive effects of TA on weaned piglets can be attributed to its polyphenolic hydroxyl structure, which exhibits strong physiological properties such as anti-diarrhea, bacteriostasis, and antioxidant activities [16,17]. Besides, TA have found to have similar functions as a prebiotic, capable of regulating gut microbiota [18].…”
Section: Introductionmentioning
confidence: 99%
“…The invasion of S. pullorum disrupts the mucus layer and facilitates the spread of harmful substances ( 37 39 ). The protective effect of TA on the intestinal barrier function of broiler chickens infected with S. pullorum was evaluated in this study based on the antimicrobial properties of TA and the regulation of tight junction proteins ( 13 , 20 ). The gene expression of intestinal claudin-1, occludin, ZO-1, and MUC2, as well as the number of goblet cells, were found to be significantly reduced as a result of S. pullorum infection.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented above demonstrate TA's effective antimicrobial activity and biosafety. Furthermore, TA has been shown to effectively reduce damage to the intestinal mucosa caused by oxidative stress and inflammatory responses ( 16 , 17 ), improve gut microbial composition, and enhance intestinal barrier function ( 18 20 ). Therefore, TA may have a preventive effect against PD and could alleviate the intestinal damage caused by S. pullorum .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary TA can also alleviate tissue inflammation and protect intestinal health by lowering the mRNA levels of tissue inflammation elements and increasing the mRNA levels of intestinal intact proteins in broilers [ 11 , 12 , 13 ]. It has been shown that TA can alleviate the inflammation of broilers with NE conditions and enhance the antioxidative ability by activating the Nrf2-Keap1 signaling pathway in rats [ 14 , 15 , 16 , 17 ]. However, whether TA could improve antioxidant capacity and alleviate oxidative stress through the Nrf2-Keap1 signaling pathway in broilers with NE condition has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%